Fracture strength of cad-cam milled polyetheretherketone (PEEK) post-cores vs conventional post-cores; an in vitro study - Direk, Ayetullah; Tekin, Samet; Khurshid, Zohaib (Peerj Inc, 2024)
Background. . The aim of this study was to compare the fracture strength and fracture modes of post-cores produced with CAD-CAM from modified polyetheretherketone (PEEK) materials with other custom-produced post-cores. Methods. . Sixty human mandibular first premolars with equal root sizes were used. The teeth were divided into six groups (n = 10), and root canal treatment was performed. The teeth were separated from the roots over 2 mm from the cemento-enamel junction. As a result of the decoronation process, a 1 mm wide shoulder line was obtained for all teeth. For the fracture strength test, 10 mm deep post spaces were created on the teeth with a 1.6 mm diameter driller. Post-core groups consisted: everStick (R) (R) glass fiber post-core (Group GF), zirconia post-core (Group Z), metal (Cr-Co) post-core (Group M), PEEK post-core without filler (Group UP), PEEK post-core with 20% TiO2 2 Filler (Group TP), and post-core with 20% ceramic filler (Group CP). Following the application of posts to post spaces, copings were created and cemented on the samples. With the universal tester, a force was applied to the long axis of the tooth with a slope of 135 degrees. degrees . The mean fracture strength (N) between the groups was statistically evaluated using one-way ANOVA, and pairwise mean differences were detected using post hoc Tukey's HSD test among the groups. Results. . According to the results of the statistical analysis, a significant difference was found between the groups in terms of mean fracture resistance (p p < 0.05). Group Z (409.34 +/- 45.72) was significantly higher than Group UP (286.64 +/- 37.79), CP (298.00 +/- 72.30), and TP (280.08 +/- 67.83). Group M (376.17 +/- 73.28) was significantly higher than Group UP (286.64 +/- 37.79) and Group TP (280.08 +/- 67.83). There were no statistically significant differences between the means of the other groups (p p > 0.05). Among all the groups, Group Z exhibited a higher prevalence of repairable failure modes, while the rest of the groups predominantly experienced irreparable failure modes. Conclusion. . In our study, zirconia and metal post-core samples showed higher average fracture strength values than PEEK post-cores groups. Repairable failure modes were more common in the zirconia post-cores, whereas the opposite was observed in the other groups. Further experimental and clinical trial studies are needed before PEEK materials can be used as post materials in the clinic.
Keywords: Fixed prosthodontics; Polyetheretherketone; Zirconia; Fracture strength; Post-core; CAD-CAM